2001
DOI: 10.1006/jabr.2001.8944
|View full text |Cite
|
Sign up to set email alerts
|

The Pure Symmetric Automorphisms of a Free Group Form a Duality Group

Abstract: The pure symmetric automorphism group of a finitely generated free group consists of those automorphisms which send each standard generator to a conjugate of itself. We prove that these groups are duality groups.  2001 Elsevier Science

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…By [Brady et al 2001], G is a duality group of dimension n −1. By the main result of [Orlandi-Korner 2000], the class [χ ] is in 1 (G) c if and only if exactly one of the following holds:…”
Section: By [Mccool 1986] G Is Finitely Presented With Relationsmentioning
confidence: 99%
“…By [Brady et al 2001], G is a duality group of dimension n −1. By the main result of [Orlandi-Korner 2000], the class [χ ] is in 1 (G) c if and only if exactly one of the following holds:…”
Section: By [Mccool 1986] G Is Finitely Presented With Relationsmentioning
confidence: 99%
“…See [Dam16] for a discussion of the many guises of these groups. Some topological properties known for PΣAut n include that is has cohomological dimension n − 1 [Col89], it is a duality group [BMMM01] and its cohomology ring has been computed [JMM06].…”
Section: Introductionmentioning
confidence: 99%
“…Collins [4] proved that PΣ n has cohomological dimension n − 1; it also follows from his work that PΣ n is F P ∞ . Later, Brady-McCammond-Meier-Miller [1] showed that PΣ n is a duality group, and Jensen-McCammond-Meier [7] determined completely the structure of the cohomology ring of PΣ n for n ≥ 3.…”
Section: Introductionmentioning
confidence: 99%